2015
DOI: 10.30843/nzpp.2015.68.5800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezing of <i>Neonectria ditissima</i> inoculum on its pathogenicity

Abstract: The fungus Neonectria ditissima causes European canker of apple To determine the pathogenicity of different isolates conidial inoculum of each isolate needs to be prepared Freezing inoculum ensures that conidia do not germinate before inoculation and facilitates screening of large numbers of isolates In this study conidial suspensions of three different isolates and field conidia collected from apple cankers were used to inoculate dormant potted 1yearold Royal Gala trees in a glasshouse Each conidial suspensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Inoculum that had been frozen for 462 days, and which had been thawed and re-frozen twice (treatment 52), still resulted in 100% canker expression in both 'Braeburn' and 'Royal Gala' cultivars despite having only 6% germination. Scheper et al (2015) found that the viability of N. ditissima spores suspended in Tween® water was not affected by freezing at -20 o C for a short period of 3 days and the results of the current study are consistent with this earlier work. However, results from recent work (2018) showed that germination of N. ditissima conidia decreased more rapidly (from 84 to 0% in an 8-week period) if they were stored frozen in a mixture of the surfactant Tween® (0.05%) and…”
Section: Discussionsupporting
confidence: 92%
“…Inoculum that had been frozen for 462 days, and which had been thawed and re-frozen twice (treatment 52), still resulted in 100% canker expression in both 'Braeburn' and 'Royal Gala' cultivars despite having only 6% germination. Scheper et al (2015) found that the viability of N. ditissima spores suspended in Tween® water was not affected by freezing at -20 o C for a short period of 3 days and the results of the current study are consistent with this earlier work. However, results from recent work (2018) showed that germination of N. ditissima conidia decreased more rapidly (from 84 to 0% in an 8-week period) if they were stored frozen in a mixture of the surfactant Tween® (0.05%) and…”
Section: Discussionsupporting
confidence: 92%
“…The conidia were similar to field-collected conidia, with >75% of the conidia multi-celled and only 5% single-celled. The suspension was frozen at -20˚C for 1 week (Scheper et al 2015).…”
Section: Trial Design and Inoculationmentioning
confidence: 99%
“…To facilitate infection with low-virulent isolates, the known susceptible apple accession 'Royal Gala' was chosen (Scheper et al 2015;Amponsah et al 2017;Scheper et al 2018). Similarly, rasp wounds were used to optimise the chance of infection with low-virulent isolates, as larger wounds lead to shorter incubation periods and higher infection rates (Walter et al 2016).…”
Section: Apple Host and Wound Selectionmentioning
confidence: 99%
“…Conversely, the N. ditissima population varies in virulence on the apple host (Scheper et al 2015) and conidial morphology (Scheper et al 2014). Similarly, differential host-pathogen interactions in the Malus-N. ditissima pathosystem have been observed (Scheper et al 2017).…”
Section: Introductionmentioning
confidence: 99%